Biomedical and Pharmaceutical Application of Fish Collagen and Gelatin: A Review - Jeevithan, Elango; Qingbo, Zhao; Bao, Bin; Wu, Wenhui (Journal of Nutritional Therapeutics, 2013)
In last decade, more research has been conducted in order to find the better way for utilizing the wastes product generated from food processing industries. The increasing demand of industrial by-products is one of the main reasons for the conversion of these wastes into valuable products. Among the different valuable products from the waste, the extraction of collagen and gelatin could be a better way of utilizing the wastes, due to their effective applications in biomedical and pharmaceutical industries. The most abundant source of collagen and gelatin are land-based animals, such as cow and pig. However, the extraction of collagen and gelatin from non-mammalian sources such as fish has been high influences in current society due to some religious and disease transmission issues. Many studies have dealt with the extraction and functional properties of collagen and gelatin from fish wastes. The present work is a compilation of information on biomedical and pharmaceutical application of collagen and gelatin from fish processing wastes.